2000
DOI: 10.1054/bjoc.2000.1480
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a schedule-dependent deleterious interaction between paclitaxel, vinblastine and cisplatin (PVC) in the treatment of advanced transitional cell carcinoma

Abstract: A phase II study to evaluate the efficacy and toxicity of the combination of vinblastine, paclitaxel and cisplatin (PVC) in previously untreated patients with advanced transitional cell carcinoma. Chemotherapy naive patients with locally advanced or metastatic transitional cell carcinoma received the intravenous combination of paclitaxel 175 mg/m 2 over three hours followed by cisplatin 70 mg/m 2 over 3 hours on day 1 and vinblastine 3 mg/m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…However, observed inconsistencies in treatment outcomes may be due to the widely varying chemotherapeutic drug concentrations and radiation-absorbed doses used (7)(8)(9)(10). In addition, there is evidence that optimization of radiation dose and drug concentration, and the time sequence for administering drugs and radiation, play important roles in treatment responses both in vitro and in vivo (4,(11)(12)(13). Also, regardless of the quality of radiation used, the wide variability in drug toxicity in normal cells of different histologies has to be considered, with favor given to the most sensitive tissue in chemoradiotherapy (14).…”
mentioning
confidence: 99%
“…However, observed inconsistencies in treatment outcomes may be due to the widely varying chemotherapeutic drug concentrations and radiation-absorbed doses used (7)(8)(9)(10). In addition, there is evidence that optimization of radiation dose and drug concentration, and the time sequence for administering drugs and radiation, play important roles in treatment responses both in vitro and in vivo (4,(11)(12)(13). Also, regardless of the quality of radiation used, the wide variability in drug toxicity in normal cells of different histologies has to be considered, with favor given to the most sensitive tissue in chemoradiotherapy (14).…”
mentioning
confidence: 99%
“…Indeed, CYP3A4 induction by vinblastine may provide a plausible explanation for the outcomes of 2 earlier clinical studies involving this drug. 33,34 For example, it was reported that treatment of patients with testicular cancer using a combination regimen of cisplatin, vinblastine, and bleomycin resulted in a 30% increase in the clearance of antipyrine, which lasted for 6 weeks. 34 Although antipyrine is metabolized by several CYP isoenzymes, CYP3A4 is responsible for the formation of a major metabolite, 4-hydroxyantipyrine.…”
Section: Discussionmentioning
confidence: 99%
“…35 Additionally, the combination of paclitaxel, vinblastine, and cisplatin was found to be less effective and less toxic than expected in the treatment of advanced transitional cell carcinoma of the urothelium. 33 In this combination, vinblastine was administered as a bolus prior to paclitaxel, which is very extensively metabolized by CYP2C8 and CYP3A4. 36,37 Thus, induction of the CYP3A4-mediated metabolism of paclitaxel by vinblastine could contribute to the low response rate and the low incidence of peripheral neuropathy reported.…”
Section: Discussionmentioning
confidence: 99%
“…The last study was comprised of patients with normal and poor renal function (Hussain et al, 2001). The association of paclitaxel, vinblastine and cisplatin, however, resulted in a poor efficacy (Mulatero et al, 2000). Another new approach studied, with preliminary encouraging results, consisted of a sequential schedule with doxorubicin and gemcitabine followed by ifosfamide, paclitaxel and cisplatin (Dodd et al, 2000).…”
Section: Discussionmentioning
confidence: 99%